Triptolide Inhibits Th17 Response by Upregulating microRNA-204-5p and Suppressing STAT3 Phosphorylation in Psoriasis - Qi He; Xingyue Wu; Quan Shi (Genetics Research)
Background. Psoriasis is an immune and inflammation-related skin disease. Triptolide with immunosuppressive and anti-inflammatory properties has been utilized for psoriasis treatment. However, the potential immunological mechanisms of triptolide have not been fully elucidated. Methods. Using an imiquimod (IMQ)-induced psoriatic mouse model, we detected the effects of triptolide on psoriasis-like lesions including scales, thickening, and erythema. Methyl thiazol tetrazolium (MTT) cytotoxicity assay was performed for evaluating the influence of triptolide on cell viability. Gene expression at mRNA and protein levels were examined by reverse transcription-quantitative polymerase chain reaction and Western blot analysis, respectively. The combination between microRNA-204-5p (miR-204-5p) and signal transduction and transcription activator-3 (STAT3) was confirmed by luciferase reporter assay. Enzyme-linked immunosorbent assay was conducted to examine interleukin (IL)-17 and interferon-γ (IFN-γ) levels using corresponding kits. Hematoxylin and eosin staining was used for the visualization of epidermal thickness. Flow cytometry analysis was employed for examining T helper (Th) 17 cells. Results. Triptolide ameliorated IMQ-induced psoriatic skin lesions manifested by the decreased psoriasis area and severity indexes (PASI) scores. Triptolide inhibited Th17 cell differentiation from splenocytes. Additionally, triptolide elevated miR-204-5p expression, whereas it downregulated STAT3 expression levels both in vitro and in vivo. Moreover, miR-204-5p directly targeted STAT3 in HaCaT cells. Furthermore, triptolide repressed the expression of proinflammatory cytokines in IMQ-evoked psoriasis-like mice. Conclusion. Triptolide inhibits STAT3 phosphorylation via upregulating miR-204-5p and thus suppressing Th17 response in psoriasis.